Effect of different heat ameliorating measures on the micro-climate of buffalo sheds during hot-dry summer - VERMA, K K; SINGH, MUKESH; DUTT, TRIVENI; GAUR, G K; PATEL, B H M; BHARTI, P K; NARWARIA, U S; VERMA, M R; CHAUDHARY, J K (The Indian Journal of Animal Sciences, 2016)
Present investigation studied the effect of heat ameliorating measures on micro-climate of sheds of Murrah buffalo heifers during hot dry summer. Buffalo heifers (24) were categorised in 4 groups (6 in each), viz. control (T0), cooling jacket (T1), cooling jacket+forced ventilation (T2) and sprinklers+forced ventilation (T3). Daily minimum and maximum and dry and wet bulb temperatures of both micro and macro-climate were measured at 10.00 AM and 2.00 PM of Indian Standard Time (IST) by using maximum and minimum and dry and wet bulb thermometer, respectively. Significant reduction in maximum temperature was observed in T3, T2 and T1 groups than control group. However, significantly higher minimum temperature was found in T0 group as compared to T3, T2 and T1 respectively. Relative humidity (RH) was significantly lower in T3 and T2 (65.67±0.48 and 65.97±0.53%, respectively) than T0 (68.51±0.56%) group at 10.00 AM whereas, at 2.00 PM significant reduction in RH was observed in T3, and T2 (55.31±0.51 and 57.20±0.62) than T0 (58.96±0.63%) group. During peak hot periods, significantly lower Temperature humidity Index (THI) was found in T3, T2 and T1 than T0 group. However, at 10.00 AM significant reduction in THI was found in T3 and T2 groups than T0 group. The findings of the present study indicated that forced ventilation along with sprinklers and cooling jacket had helped in protecting the animals from thermal stress under loose housing system during hot-dry summer.